The Effect of Gobak sodor Games on the Gross Motor Skills of Running in Children with Mild Intellectual Disabilities at the Budhi Surabaya Special School - Moch Fajar Ramadhan; Luqmanul Hakim (Journal of Comprehensive Science, 2026)
This research is motivated by the importance of developing gross motor skills in children with mild intellectual disabilities through adaptive physical education that is engaging and appropriate to students’ characteristics. Based on preliminary observations at Budhi Special School in Surabaya, students’ gross motor skills, particularly running ability, were still relatively low because learning activities tended to use simple and less varied movement exercises. As a result, students easily became bored and lacked motivation to participate actively in physical activities. Therefore, traditional games such as gobak sodor can be used as an alternative learning medium that is more enjoyable and capable of stimulating students’ physical movement. This study aims to analyze the effect of the gobak sodor traditional game on improving gross motor skills, especially running ability, in children with mild intellectual disabilities. The research employed a quantitative approach using a quasi-experimental method with a one-group pretest–posttest design. The sample consisted of 20 students selected through purposive sampling. The research instrument used was a 40-meter sprint test to measure students’ gross motor skills. Data were analyzed using descriptive statistics and a paired sample t-test with the assistance of SPSS version 23 software. The results showed a significant difference between the pretest and posttest results with a significance value of 0.032 (<0.05), indicating that the gobak sodor game has a significant effect on improving students’ gross motor skills. Thus, the gobak sodor traditional game is effective as a learning method to enhance the gross motor skills of children with mild intellectual disabilities.